Reaction of 2-propanol with ozone in aqueous media. (1st January 2018) - Reisz, Erika; von Sonntag, Clemens; Tekle-Röttering, Agnes; Naumov, Sergej; Schmidt, Winfried; Schmidt, Torsten C.
Abstract: This paper deals with reactions occurring in the aqueous system of 2-propanol/ozone. The considered reactions are discussed from thermodynamic and kinetic points of view. The major finding refers to the fact that 2-propanol reacts with O3 mainly via hydride transfer: (HO)(H3 C)2 CH + O3 → [(HO)(H3 C)2 C + + HO3 − ]cage → (HO)(H3 C)2 C + + HO3 − → (H3 C)2 CO + H2 O + O2 Arguments supporting this proposed mechanism are: high exergonicity of reaction (ΔG = −234 kJ mol −1 for the first two steps), low HO yield - (2.4 ± 0.5)% and high acetone yield - (87.2 ± 1.5)%. Other oxidation products detected within the system are acetaldehyde - (1.4 ± 0.1)%, formaldehyde - (4.0 ± 0.1)%, acetic acid - (2.8 ± 0.2)%, formic acid - (0.6 ± 0.2)% and hydrogen peroxide - (1.5 ± 0.1)%. The temperature dependence of the second order rate constant for the reaction 2-propanol + O3 → products is ln kII = 29.64–8500 × T −1 . The activation energy and pre-exponential factor derived from this relationship are (71 ± 3) kJ mol −1 and (7.5 ± 6.4) × 10 12 M −1 s −1, respectively. At 23 °C, the second order rate constant is kII = (2.7 ± 0.1) M −1 s −1 . The low reaction rate can be explained by the transfer of one hydride ion from 2-propanol to electrophilic ozone. Graphical abstract: Image 1 Highlights: Interaction pathways among 2-propanol and O3 /HO in aqueous media are discussed. The approach is both thermodynamically and kinetically. The main pathway is triggered by an hydride transfer from 2-propanol to O3 . When O3 attack occurs at CH bond, hydride transfer is expected to be favoured.